Inhibition of p70 Ribosomal S6K1 Protects the Myocardium against Ischemia/Reperfusion-Induced Necrosis through Downregulation of RIP3 - Hui Shang; Jinjin Shi; Jun Zhu; Yunfeng Guo; Xiaoyan Wang (Frontiers in Bioscience-Landmark)
Background: Myocardial ischemia-reperfusion (I/R) injury refers to cell damage that occurs as a consequence of the restoration of blood circulation following reperfusion therapy for cardiovascular diseases, and it is a primary cause of myocardial infarction. The search for nove therapeutic targets in the context of I/R injury is currently a highly active area of research. p70 ribosomal S6 kinase (S6K1) plays an important role in I/R induced necrosis, although the specific mechanisms remain unclear. Objective: This study aims to explore the effects of inhibiting S6K1 on myocardial I/R injury and its potential mechanisms. Methods: A rat myocardial I/R model was created and treated with the S6K1-specific inhibitor PF-4708671. Hematoxylin-eosin (H&E) staining was applied to evaluate the pathological changes in cardiac tissues. 2,3,5-triphenyltetrazolium chloride (TTC) staining was used to measure the area of myocardial infarction (MI). Left ventricular systolic pressure (LVSP), left ventricular end-diastolic pressure (LVEDP), the maximum rate of increase in left ventricular pressure (+dp/dtmax), and the maximum rate of the decrease in left ventricular pressure (-dp/dtmax) were measured using ultrasonic echocardiography. The expression levels of cardiac troponin-1 (cTn-1), lactate dehydrogenase (LDH), creatine kinase MB (CK-MB), and aspartate aminotransferase (AST) were determined by enzyme-linked immunosorbent assay (ELISA). Terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) staining and propidium iodide (PI) staining were used to examine the apoptosis and necrosis of myocardial tissues. The expressions of apoptotic-related proteins, and key molecules of necrosis were detected by western blot. The relationship between S6K1 and receptor-interacting protein kinase 3 (RIP3) was analyzed by immunoprecipitation. Results: Inhibition of S6K1 reduces I/R-induced myocardial tissue damage, improves myocardial function, and inhibits myocardial tissue necrosis (p < 0.05). In addition, RIP3 is a direct target of S6K1, and activation of RIP3 blocked the protective effect of the S6K1 inhibitor PF-4708671 against myocardial I/R injury (p < 0.05). Conclusion: Inhibition of S6K1 protects against myocardial I/R injury by down-regulating RIP3, suggesting that targeting S6K1 may offer a novel approach for intervention in myocardial I/R injury.